Pelaksanaan Kampus Mengajar Angkatan 4 SDN 2 Kedungwaru - Ari Indriani; Wanda Revana Putri; Siti Jumaria; Meilisa Khonirma Sari; Mu'izzu Nazaka Ramadha; Mahar Devi Octaviana (IKIP PGRI Bojonegoro, 2023)
Abstract: The Teaching Campus batch 4 which is located at SD N 2 Kedungwaru has the aim of knowing the implementation of the Teaching Campus batch 4 program at SDN 2 Kedungwaru. The type of research used is descriptive qualitative research. This research was carried out starting from August 1, 2022 at SD N 2 Kedungwaru located in Kunduran District, Blora Regency, Central Java. The data collection technique uses the results of the Teaching Campus batch 4 activities at SD N 2 Kedungwaru. The work plans carried out include literacy before learning by reading books that have been prepared by students or bringing reading books from home, reading corners, calistung, adding book collections for the